La philosophie contemporaine / Contemporary philosophy
X, 550 p.
Keywords: The present publication is a continuation of two earlier series of chronicles, Philosophy in the Mid-Century (Firenze 1958/59) and Contemporary Philosophy (Firenze 1968), edited by Raymond Klibansky. As with the earlier series the present chronicles purport to give a survey of significant trends in contemporary philosophi cal discussion. The time space covered by the present series is (approximately) 1966-1978. The need for such surveys has, I believe, increased rather than decreased over the last years. The philosophical scene appears, for various reasons, more complex than ever before. The continuing process of specialization in most branches, the emergence of new schools of thought, particularly in philosophical logic and the philosophy of language, the convergence of interest (though not necessarily of opinion) of different traditions upon certain prob lems, and the increasing attention being paid to the history of philosophy in discussions of contemporary problems are the most important contributory factors. Surveys of the present kind are a valuable source of knowledge of this complexity and may as such be of assistance in renewing the understanding of one's own philosophical problems. The surveys, it is to be hoped, may also help to strengthen the Socratic element of modern philosophy, the dialogue or Kommunikationsgemeinschaft. So far, four volumes have been prepared for the new series. The present chronicles in Philosophy of Science (Vol. 2) follow the chronicles in the Philosophy of Language and Philosophical Logic (Vol.